2021
DOI: 10.1111/gcbb.12802
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and biochar influence simazine decomposition and leaching

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Even the inhibitory effects of G. versiforme inoculation on plant height, stem diameter, and biomass of red-orange tissue cultured seedlings were reported [ 26 ]. The possible reason is that under limited nutrient conditions, the development of AM fungi not only requires the host plant to provide carbohydrates but also competes with the host plant for nutrients, resulting in no effect or even negative effect on the growth of the host plant [ 27 ]. On the other hand, the regulation of host plant growth through AM fungal inoculation is influenced by the specific genus and species of the inoculated fungi [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even the inhibitory effects of G. versiforme inoculation on plant height, stem diameter, and biomass of red-orange tissue cultured seedlings were reported [ 26 ]. The possible reason is that under limited nutrient conditions, the development of AM fungi not only requires the host plant to provide carbohydrates but also competes with the host plant for nutrients, resulting in no effect or even negative effect on the growth of the host plant [ 27 ]. On the other hand, the regulation of host plant growth through AM fungal inoculation is influenced by the specific genus and species of the inoculated fungi [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biochar Preparation, Soil, and 14 C-Labeled Simazine Unmodified biochar was produced from wheat (Triticum aestivum L.) straw collected from the Henfaes Research Centre Wales, North Wales, United Kingdom (53 • 140N; 4 • 100W). The preparation process was introduced by Cheng et al (2021). The iron modification process was mainly completed according to the method developed by Wu et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, biochar application as an amendment for remediation of soil and water pesticide pollution has attracted increasing attention worldwide. Several studies indicated that biochar could effectively increase the adsorption of simazine in the soil, thus decreasing its risk of leaching into the environment and also reducing its risk of being directly being up-taken by plants (Jones et al, 2011a;Eibisch et al, 2015;Cheng et al, 2021). Simultaneously, some studies have reported that biochar inhibits simazine biodegradation (Cheng et al, 2017a) and reduces simazine efficacy for controlling weeds or killing pests.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, soil inoculated with arbuscular mycorrhizal fungi and biochar efficiently reduced the concentration of simazine. This study attributed these results to variation in the soil's sorption capacity due to biochar amendment and the inoculation of fungal strains [93]. A soil yeast was isolated from the soil, identified as Lipomyces starkeyi, and its degradation efficiency was tested against s-triazine herbicides.…”
Section: Potential Microbial Species Employed For Biodegradation Of S...mentioning
confidence: 99%